In situ investigation of carbon gasification using ultrabroadband coherent anti-Stokes Raman scattering - Ran, Yang; Boden, Andre; Kuester, Felix; An, Fengbo; Richter, Andreas; Guhl, Stefan; Nolte, Stefan; Ackermann, Roland (Applied Physics Letters, 2021)
The gasification of carbonaceous feedstocks usually takes place in high-pressure, high-temperature reactors, making it difficult to have direct access to the reaction site. Since the greenhouse gas CO2 is a major component in gasification, there is an urgent need for a better understanding of these processes. In this study, we investigate carbon gasification in a CO2 atmosphere using the ultrabroadband, coherent anti-Stokes Raman spectroscopy (CARS). In contrast to conventional three beam CARS, this approach allows the simultaneous determination of the temperature of the CO2 atmosphere and the concentration of the reaction product CO. We show that temperature drop and increase in CO are directly linked to the feedstock conversion measured by thermogravimetric analysis. Due to gasification, a considerable temperature drop of up to 200 K was measured, which was predicted by simulations in the literature but has not been confirmed experimentally yet.
CRIS-Team Scopus Importer:2023-04-20